(untitled) (Research, Society and Development, 2022)
The consumption of smokeless tobacco (TSF) causes several damages to health, mainly in the oral cavity, being a predisposing factor to cancer and resulting in many lesions, this makes it necessary to know how to identify which are the main soft tissue lesions caused by TSF. The aim of this study is to analyze the main oral soft tissue injuries associated with the consumption of TSF. The research was based on an integrative literature review, the bibliographic survey was carried out with the help of the Health Sciences Descriptors (DeCS): Smokeless Tobacco, Tobacco, Diseases of the mouth and Oral Mucosa. The following databases were used: SciELO, LILACS, VHL and PubMed. As inclusion criteria, only complete studies, in Portuguese and English, free of charge and within the time frame from 2015 to 2022. The exclusion criteria were repeated studies, simple or expanded abstracts, opinion articles or reviews, and finally, studies that were not within the theme and objective of this research. The research resulted in 27 articles analyzed, among these, 6 articles were selected to compose this study. As a result, it was shown that irritation and direct contact for long periods of oral soft tissues with tobacco, generates inflammation and epithelial stress, which makes it a predisposing factor to various oral lesions. It is concluded that the main soft tissue lesions associated with the consumption of TSF are, commonly, white lesions such as, for example, oral candidiasis, TSF keratosis, Leukoplakia, Smoker’s Melanosis and Erythroleukoplakia.